2016
DOI: 10.1038/srep19957
|View full text |Cite
|
Sign up to set email alerts
|

Impact of external medium conductivity on cell membrane electropermeabilization by microsecond and nanosecond electric pulses

Abstract: The impact of external medium conductivity on the efficiency of the reversible permeabilisation caused by pulsed electric fields was investigated. Pulses of 12 ns, 102 ns or 100 μs were investigated. Whenever permeabilisation could be detected after the delivery of one single pulse, media of lower conductivity induced more efficient reversible permeabilisation and thus independently of the medium composition. Effect of medium conductivity can however be hidden by some saturation effects, for example when pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 51 publications
4
50
0
2
Order By: Relevance
“…The researchers agree that, in biological issues resolution, the cooperation between experiments and modeling must be considered as a fundamental step [12, 16, 27, 28]. In particular, this aspect is critical and significant when one wants to investigate the interactions between the electromagnetic fields and the biological objects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers agree that, in biological issues resolution, the cooperation between experiments and modeling must be considered as a fundamental step [12, 16, 27, 28]. In particular, this aspect is critical and significant when one wants to investigate the interactions between the electromagnetic fields and the biological objects.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, with the advances in micro- and nanofabrication techniques, some microdevices are proposed for nanosecond exposure, integrated also with a microfluidic system [16, 19, 22, 23]. A typical applicator is a standard electroporation cuvette consisting of two plate parallel electrodes with a gap of 4, 2, or 1 mm [12, 13, 18, 20]. In particular, the 1 mm gap cuvette permits generating higher values of the electric field in the solution, but in such cases the matching with the 50 Ω of the pulse generator can be critical [17, 20].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present experimental data on extracellular medium conductivity effects during electroporation in the submicrosecond range (100 ns-900 ns) using mouse colon carcinoma MC38/0 cell line as a model. We superposition our data with available studies 10,11 in the nanosecond range using 25 ns pulses of 60 kV/cm. To maximize the consolidation of knowledge and to provide a reference for the described efficacies, we also cover the conventional microsecond range (100 μs × 8) pulses.…”
mentioning
confidence: 99%
“…Currents can be excited without plasma when electrodes are immersed in the electrolyte, to which a potential difference is applied ( Fig. 1(B)) [11][12][13][14][15]. These ion currents can lead to an additional charge of cell membranes, thus changing the transmembrane potential difference.…”
mentioning
confidence: 99%
“…In [11][12][13], it was experimentally shown that the critical field strength for the lysing of bacteria (prokaryotic cells) is around 0.1-1 V across the cell membrane, depending on exposure time. In [15], experimental results were given for the influence of electric fields of varying intensity and duration on cancer cells at different values for the medium's conductivity [15]. It was shown that, as the medium's salinity (conductivity) increases, the electric field at which cell death occurs begins to fall.…”
mentioning
confidence: 99%